2007
DOI: 10.1128/jvi.01217-07
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Receptor Binding Properties of Recent Human Influenza H3N2 Viruses Are Associated with Reduced Natural Killer Cell Lysis of Infected Cells

Abstract: Natural killer (NK) cell recognition of influenza virus-infected cells involves hemagglutinin (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
43
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 37 publications
1
43
0
Order By: Relevance
“…We further showed that IV infection in mice is lethal in the absence of murine Ncr1 (11). Recently, Owen et al reported that alterations in HA binding properties of recent human influenza H3N2 viruses are associated with reduced NK cell lysis of infected cells (20). The pathogenicity of IV H5N1 strains in humans has been attributed mostly or partially to antigenic changes in the IV HA that render virus-specific immunity incapable of timely response to the developing infection (9,21).…”
mentioning
confidence: 59%
“…We further showed that IV infection in mice is lethal in the absence of murine Ncr1 (11). Recently, Owen et al reported that alterations in HA binding properties of recent human influenza H3N2 viruses are associated with reduced NK cell lysis of infected cells (20). The pathogenicity of IV H5N1 strains in humans has been attributed mostly or partially to antigenic changes in the IV HA that render virus-specific immunity incapable of timely response to the developing infection (9,21).…”
mentioning
confidence: 59%
“…Reduction in affinity of human H3N2 viruses for avian receptors since the beginning of the pandemic in 1968 has meant that by the 1990s viruses with reduced ability to agglutinate chicken erythrocytes had emerged (8,9). Moreover, viruses isolated after 1999 were shown to have reduced affinity for both human and avian receptors, a feature that correlated with their poor growth properties in eggs and different cells in culture (9)(10)(11)(12)(13)(14). The evolution of the HA has resulted in at least three key changes that influence receptor binding.…”
mentioning
confidence: 99%
“…Polymer binding studies using assays similar to that presented here have been utilized extensively to investigate influenza virus binding preference (10,18,24,25,27,35,47). However, data presented herein suggest that binding preference in such assays does not correlate uniformly with the receptor determinants utilized for infection.…”
mentioning
confidence: 94%
“…Linear regression analysis of Scatchard plots was performed using Prism software (GraphPad, La Jolla, CA). The Neu5Ac␣2,3Gal␀1-4Glc␀ (2,3SL) polymer is widely utilized as the avian-like receptor analog, while the Neu5Ac␣2,6Gal␀1-4GlcNAc␀ (2,6SLN) polymer is utilized as the human-like analog (11,(24)(25)(26)35). To ensure that the different polymer backbones (lactose versus lactosamine) did not have major effects on binding affinity, we included 2,3SLN and found that viruses bound to 2,3SL and 2,3SLN with similar levels of affinity (Table 1).…”
mentioning
confidence: 99%